Pengetahuan Vasektomi Sebagai Mediator Ketimpangan Gender Terhadap Dukungan Kebijakan Vasektomi Laki-Laki Dewasa - Chindy Agustin Indriyani; Elva Nur Aini; Ita Rahayu; Tutut Mareta MD; Khoiriya Ulfa (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Male participation in family planning programs, particularly through vasectomy, remains relatively low in Indonesia. This condition is influenced not only by limited knowledge about vasectomy but also by perceptions of gender inequality that place reproductive responsibilities predominantly on women. Consequently, men's support for vasectomy-related policies is still limited. This study aims to examine the mediating role of knowledge about vasectomy in the relationship between perceptions of gender inequality and adult men's support for vasectomy policy. The study employs a quantitative approach using a survey design to analyze the relationships among the research variables. The independent variable is the perception of gender inequality, the mediating variable is the level of knowledge about vasectomy, and the dependent variable is adult men's support for vasectomy policy. Data are analyzed using mediation analysis to identify both direct and indirect effects among the variables. The proposed framework assumes that perceptions of gender inequality may encourage greater support for vasectomy policy through increased knowledge of vasectomy. The findings are expected to contribute to the development of more effective reproductive health education programs and evidence-based policies aimed at increasing male participation in family planning while promoting gender equality.